Efektivitas Pengelolaan Dana Retribusi Parkir Sebagai Sumber Pendapatan Asli Daerah Di Kota Denpasar - I Komang Raiana (Jurnal Ilmiah Raad Kertha, 2018)
Research with the theme of parking fee retribution management aims to find out (1) How Role of Parking Levy Fund In Supporting Local Original Income in Denpasar City, (2) What Factors Affect The Effectiveness Of The Management Of Parking Levy Funds As Revenue Source Of The Region In Town Denpasar. This type of research is descriptive. Data were collected by documentation method and interview. Data analysis uses effectiveness techniques and effectiveness ratio ratios. The result of the research shows that (1) Management of Retribution Fund of parking as a source of income of Denpasar Municipality has not been utilized maximally in the provision of parking facilities and improvement of fair parking services; (2) obstacles experienced in receipt of parking fees at Denpasar Municipal Parking Company a) Parking management supervision system that has not been optimal, b) there are still many parking officers who have not yet officially.